The effect of physical activity performed in the first trimester on the development of preeclampsia and gestational diabetes (Annals of Medical Research, 2021)
Aim: We aimed to investigate the effects of physical activity performed in the first trimester on preeclampsia, gestational diabetes, and other pregnancy outcomes.Materials and Methods: This prospective observational study included 205 healthy pregnant women with 11 to 13 weeks of gestation who applied to our gynecology and obstetrics outpatient clinic between April and July 2019. The demographic information of the patients was recorded and a short form of the International Physical Activity Questionnaire was used to determine physical activity levels. These pregnant women were followed until birth. A confounder control was performed with logistic regression.Results: While 16 (7.8%) of the participants developed preeclampsia, 20 (9.8%) of them developed gestational diabetes. Total physical activity levels were lower in women who developed preeclampsia. In the group that developed gestational diabetes, the number of pregnant women with low physical activity levels and the number of nulliparous pregnant women were found to be significantly higher. There was no effect of daily sitting time on preeclampsia and gestational diabetes development. Second-hour blood glucose levels were found to be higher in the group with low physical activity.Conclusion: Pregnancies complicated by gestational diabetes or preeclampsia are associated with poor pregnancy outcomes and are very important risk factors for postpartum maternal and fatal healt. Inadequate physical activity is a modifiable risk factor for the development of preeclampsia and gestational diabetes. Behavioral changes in women with insufficient physical activity levels in the first trimester may decrease the risk of gestational diabetes and preeclampsia.
Keywords: Gestational diabetes; oral glucose tolerance test; physical activity during pregnancy preeclampsia; sedentary behavior